KRITERIA KIFAYAH DAN MA'RUF NAFKAH ISTERI DAN ANAK: KAJIAN PELAKSANAAN SEMASA DI MALAYSIA: Criteria of Kifayah and Ma'ruf for Maintenance of Wife and Children: A Study on the Current Practice in Malaysia - Ahmad, Bahiyah; Azahari, Raihanah; Ab Rahman, Asmak (Jurnal Syariah, 2013)
It is obligatory for a husband in Islam, to provide his wife and children with sufficient maintenance. In this aspect, he must ensure that the maintenance provided has fulfilled the criteria determined by Islam that are kifayah and ma'ruf. It is however worth to mention that the interpretation of these concepts must be based on the current societal norms. This article analyzes how the concept of kifayah and ma'ruf have been discussed and applied in Malaysian Shariah Courts. The data for the study have been obtained from the interviews with the Sharia court judges who have been presiding matrimonial cases pertaining to family maintenance. It is eventually found that the judges have taken into consideration several criteria in their judgment to clarify and measure the kifayah and maaruf concepts which reflects that the modern socio economic conditions have been indeed incorporated.